Effect of asenapine and iloperidone on weight gain in patients of psychosis: a prospective study - Koduru Neeraja; C. Keerthi; S. Sharon Sonia (International Journal Of Community Medicine And Public Health, 2023)
Background: Second generation or atypical antipsychotics are the most commonly used effective drugs for psychotic disorders like schizophrenia. But the drawback with the use of these drugs is that they tend to cause adverse effects; among which weight gain is an important one with risk of diabetes and adverse cardiovascular events. Weight gain is less with newer atypical antipsychotics. This study was conducted to compare weight gain with two newer atypical antipsychotic drugs, Asenapine and Iloperidone Methods: It is a prospective study conducted on a total of 60 subjects who were diagnosed with schizophrenia or acute psychosis according to ICD 10 guidelines. The subjects were divided into two groups of 30 each. They received Asenapine (5-20 mg) and Iloperidone (8-24 mg) and were followed-up with weight measurements at baseline, week 1, week 3 and week 6. Results: Out of 60 subjects, 5 patients were lost to follow-up. The mean weight gain in each of the groups was 2.18±1.84 kg with Iloperidone and 1.63±1.28kg with Asenapine, which was statistically not significant. Weight gain was dose-dependent, 3.63kg mean weight gain with 15-20 mg Asenapine and 3.45 kg with 18-24 mg Iloperidone; which was statistically significant. Conclusions: Weight gain was seen with both the atypical antipsychotic drugs, Asenapine and Iloperidone; which was only of mild to moderate degree. Among the two study drugs, Iloperidone showed more weight gain than Asenapine.